Out of the shadows: mental health of Canadian armed forces veterans. Issue 4 (November 2014) - Thompson, James M.; Zamorski, Mark A.; Fikretoglu, Deniz; VanTil, Linda; Sareen, Jitender; MacLean, Mary Beth; Carrese, Pasqualina; Macintosh, Stewart; Pedlar, David
Abstract : In the past 15 years in Canada, as in other nations, the mental health of veterans has emerged as a key concern for both government and the public. As mental health service enhancement unfolded, the need for wider population studies became apparent. This paper describes the renewal of services and key findings from national surveys of serving personnel and veterans.